Pengaruh PendidikanpKeuanganoKeluarga, Kontrol Diri Dan Gaya Hidup Terhadap Minat Menabung (Santri MahasiswatPondok Pesantren Nurul IslamtBadut Karangbesuki Malang) - Ahmad Hanif Hamyanto; Hadi Sunaryo; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Saving is one of the important ways of money management. Given the importance of the role of saving, saving activities need to be familiarized and instilled in every individual, especially in adolescence to adulthood, because at this time a child begins to be given the trust to be independent in managing his finances. In this case, it has never analyzed problems related to family financial education, self-control, and lifestyle in students of the Nurul Islam Malang Islamic boarding school. PurposeAof this study is to determine andAanalyze the Effect of Family FinancialAEducation, Self-Control, and Lifestyle on the Interest in Saving for Students of Nurul Islam Islamic Boarding School Malang. The approach method that uses saturated sample techniques is nonprobability sampling, a sample collection technique using questionnaires distributed by 40 respondents. The results showed that family financial education, self-control, and lifestyle on the interest in saving for students of Nurul Islam IslamicTboarding school students had a significantOeffect on the interest in saving. The results ofPthis studyYcan be used as a reference for further researchers by further developing thePvariables under study and further developing the study with additional populations and samples. Keywords: Family Financial Education, Self-Control, Lifestyle, and Interest in Saving